Pavement maintenance optimization strategies for national road network in Indonesia applying genetic algorithm - Hamdi, H. (2017)
"6th International Workshop on Performance, Protection & Strengthening of Structures under Extreme Loading, PROTECT2017, 11-12 December 2017, Guangzhou (Canton), China"